AN ANALYSIS OF TEACHER STRATEGIES IN TEACHING READING COMPREHENSION AT SMA MUHAMMADIYAH 1 METRO ACADEMIC YEAR 2017/2018 - Desca Ariyana; Deri Sis Nanda (Universitas Bandar Lampung, 2017)
This study was conducted to know the students reading comprehension between two variable. There were two problems: (1) To know the teacher strategies in teaching reading at SMA Muhammadiyah 1 Metro. (2) To know what extent the strategies help the teacher in teaching reading comprehension at SMA Muhammadiyah 1 Metro. This study was conducted to improve whether “How do the teachers improve students’ reading comprehension at SMA Muhammadiyah 1 Metro”. The subject of this study were 28 students of the first years students of SMA Muhammadiyah 1 Metro. They were considered as the sample of the whole population. It was assumed that teacher strategies and reading comprehension in english was very important in learning English. As doing assigments or home works, preparing the lesson at home, using a spare time for reading etc. it would be useful for improvement of their ability in reading comprehension. This study was to verify the hypothesis that there was reading subject is one important material same as the other skills likes writing, speaking and listening. This study was obtained by field research by observation. The result of this research were collected by observation and interview to the teacher and students.